Analisis Soal Computer Based Test untuk Tes Potensi Akademik dan Biologi Manusia - Adelia Adelia; Tiur Gantini; Victor Kurniawan (Maranatha University Press, 2021)
Education providers, one of which is a private university in Bandung, conducts entrance exams for student participants through a computer-based test system. In the entrance examination, which is carried out is a test of academic potential and human biology. Every question that belongs to both the TPA and human biology questions is stored in the university's computer-based test system. The saved questions can be used at any time, during the entrance examination period. The stored questions need to be analyzed and reviewed, with the aim that the questions can be used properly and can maintain the quality of the questions given to each examinee. In this study, an analysis of the level of difficulty and effectiveness of the distractor will be carried out. This analysis is carried out using data from 2018 to 2020 stored in the system.